Knowledge management and business performance of casual dining restaurants in Malaysia - Othman, Abdul Rahim; Don, Mohd Sobri (2012)
This study examines the relationship between knowledge management and business performance in a restaurant industry. A theoretical model that is based on the resource-based view of the firm is developed and tested empirically. The model includes three main components of knowledge management which are knowledge actualization, knowledge dissemination and responsiveness to knowledge where the performance of the restaurant is measured based on profitability and also customer satisfaction from the perspective of managers. Survey data of 164 casual dining restaurants’ managers in the Klang Valley, Malaysia was used to test the relationship between the main constructs in the study.Analysis reveals that only responsiveness to knowledge has a positive relationship with business performance.These findings suggest that profitability and customer satisfaction of the casual dining restaurant in Malaysia depend on how well the restaurant responds to knowledge of its customers, competitors and market conditions.